2018
DOI: 10.1016/j.bbmt.2017.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cytomegalovirus Viral Load on Probability of Spontaneous Clearance and Response to Preemptive Therapy in Allogeneic Stem Cell Transplantation Recipients

Abstract: The optimal viral load threshold at which to initiate preemptive cytomegalovirus (CMV) therapy in hematopoietic cell transplantation (HCT) recipients remains to be defined. In an effort to address this question, we conducted a retrospective study of 174 allogeneic HCT recipients who underwent transplantation at a single center between August 2012 and April 2016. During this period, preemptive therapy was initiated at the discretion of the treating clinician. A total of 109 patients (63%) developed CMV viremia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 35 publications
4
55
1
1
Order By: Relevance
“…A total of 174 consecutive HCT patients transplanted between September 2012 and April 2016 were reviewed. The general characteristics of this cohort have been published previously . Of these patients, 78 (44.8%) patients were treated for an episode of early CMV reactivation with a median viral load at initiation of therapy of 700 IU/mL (IQR, 348‐1398).…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…A total of 174 consecutive HCT patients transplanted between September 2012 and April 2016 were reviewed. The general characteristics of this cohort have been published previously . Of these patients, 78 (44.8%) patients were treated for an episode of early CMV reactivation with a median viral load at initiation of therapy of 700 IU/mL (IQR, 348‐1398).…”
Section: Resultsmentioning
confidence: 56%
“…Current treatment guidelines state the use of maintenance therapy could be considered following clearance of DNAemia; yet, the effectiveness of maintenance therapy is not well defined. The rate of recurrence after clearance of initial CMV DNAemia can be as high as 50‐70% in allogenic HCT patients and there are no data indicating that maintenance therapy does indeed reduce such risk of recurrence. Prolonged duration of antiviral therapy can be associated with adverse events, emergence of antiviral resistance, and significant added cost.…”
Section: Introductionmentioning
confidence: 99%
“…It should be highlighted that both this approach and ours spare the need for PET administration in a notable percentage of patients who are capable of controlling CMV replication by themselves, thus potentially reducing the toxicity inherent in the use of nucleoside analog anti‐CMV drugs. Other studies, in contrast, advocate initiating PET at very low CMV DNA loads (<150 IU/mL) aimed at reducing the length of antiviral treatment needed to clear CMV DNAemia . Unfortunately, a direct comparison between these studies and ours is not straightforward because of a number of factors, including the use of different PCR assays and criteria for initiation of PET and patients’ baseline and post‐transplant characteristics in each cohort.…”
Section: Discussionmentioning
confidence: 93%
“…Two recent reports support the suitability of this approach; Tan and colleagues showed that initiation of PET at low CMV DNA loads results in shorter episodes of CMV DNAemia and courses of antiviral therapy. In turn, Camargo et al concluded that CMV DNA peak levels ≥ 150 IU/mL associate with a drastically reduced probability of spontaneous CMV DNAemia clearance . PET initiation at low CMV DNA levels may lead to unnecessary use of antivirals for episodes that might clear spontaneously.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation